2019
DOI: 10.1038/s41385-018-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminth infection promotes IL-5- and CD4+ T cell-dependent immunity in the lung against migrating parasites

Abstract: The ability of helminths to manipulate the immune system of their hosts to ensure their own survival is often credited with affecting responses to other pathogens. We undertook co-infection experiments in mice to determine how infection with the intestinal helminth Heligmosomoides polygyrus affected the parasitological, immunological and physiological outcomes of a primary infection with a distinct species of helminth; the lung migratory parasite Nippostrongylus brasiliensis. We found that migrating N. brasili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
0
39
1
Order By: Relevance
“…cells, which orchestrated IL-5-mediated eosinophil-dependent larval killing (68). In addition, our results suggest that HDMinduced reduction in Ascaris numbers and arrested development is dependent on eosinophils in the lungs driven by CD4 + T cells (see Figure 6).…”
Section: Discussionmentioning
confidence: 59%
“…cells, which orchestrated IL-5-mediated eosinophil-dependent larval killing (68). In addition, our results suggest that HDMinduced reduction in Ascaris numbers and arrested development is dependent on eosinophils in the lungs driven by CD4 + T cells (see Figure 6).…”
Section: Discussionmentioning
confidence: 59%
“…In fact, in the absence of STAT1 we found an acutely increased expression of FIZZ-1, thus it may be that recently hatched larvae are rapidly expelled from the intestine, and therefore lungs, due to an increase in mucus production and fewer larvae may reach blood vessels for dissemination to other organs. In line with this Filbey et al found that migrating N. brasiliensis larvae were killed in the lungs of mice co-infected with H. polygyrus, and the lung pathology associated with N. brasiliensis larval migration was reduced by robust Th2 immunity [58]. Finally, Esser-von Bieren et al suggested a novel IL-4Rα-independent mechanism of M2 activation that is antibody-dependent and mediates both anti-helminth immunity and tissue disruption caused by migrating H. polygyrus larvae [59].…”
Section: Discussionmentioning
confidence: 60%
“…LPS from Escherichia coli O111 [153], bacterial polysaccharide A [154], oligodeoxynucleotides with bacterial CpG motifs [155], flagellin B [156], short-chain fatty acids [47], D-tryptophan [157] and the neutrophil-activating protein from Helicobacter pylori [158] all suppressed airway eosinophilia and type 2 T-helper cell-mediated immune responses in murine models of AAD. Likewise, several molecules from the parasite helminths have now been identified, among which excretory-secretory (ES)-62 and cystatin (AvCystatin) from Acanthocheilonema vitae, TGF-β mimic (TGM) and Heligmosomoides polygyrus alarmin release inhibitor (HpARI) from H. polygyrus and IL-4-inducing principle from schistosome eggs (IPSE) are the most promising, with effects in allergic asthma models [159][160][161][162][163].…”
Section: Implications For the Development Of Novel Therapiesmentioning
confidence: 99%